2019
DOI: 10.1371/journal.pone.0211344
|View full text |Cite
|
Sign up to set email alerts
|

HIV virologic failure and its predictors among HIV-infected adults on antiretroviral therapy in the African Cohort Study

Abstract: IntroductionThe 2016 WHO consolidated guidelines on the use of antiretroviral drugs defines HIV virologic failure for low and middle income countries (LMIC) as plasma HIV-RNA ≥ 1000 copies/mL. We evaluated virologic failure and predictors in four African countries.Materials and methodsWe included HIV-infected participants on a WHO recommended antiretroviral therapy (ART) regimen and enrolled in the African Cohort Study between January 2013 and October 2017. Studied outcomes were virologic failure (plasma HIV-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
83
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 41 publications
18
83
3
Order By: Relevance
“…Consistent with our findings, data from a large cohort study conducted in East Africa and Nigeria showed that younger age, single marital status and female gender were independently associated with virologic failure and immunologic failure [ 25 ]. In addition, at a tertiary hospital such as UATH, the clinicians who manage patients are largely resident doctors who rotate through various departments, including the HIV treatment clinic, with variable supervision.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our findings, data from a large cohort study conducted in East Africa and Nigeria showed that younger age, single marital status and female gender were independently associated with virologic failure and immunologic failure [ 25 ]. In addition, at a tertiary hospital such as UATH, the clinicians who manage patients are largely resident doctors who rotate through various departments, including the HIV treatment clinic, with variable supervision.…”
Section: Discussionsupporting
confidence: 90%
“…Although some studies have examined predictors of immunologic failure among patients failing first-line regimens, there is a paucity of data from sub-Saharan Africa [ 20 25 ]. In a retrospective multi-site study evaluating long-term outcomes of patients receiving ART in a treatment program in Nigeria, authors indicated that older age, ART regimen, lower CD4 count, higher VL and inadequate adherence were predictors of virologic failure, while female sex and lower baseline CD4 were predictive of immunologic failure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated VL indicates poor adherence or resistance [2628]. The overall proportion of non-suppression was higher compared to the study conducted in Uganda 11% [20], Systematic review on viral non suppression rate in low or middle-income countries of the pooled estimate had 16% [29], African cohort 9% [30], Nepal 9.92% [31] and Ethiopia 10.4% (self-report) [6] and 19% [1] and 11.5% in Mekelle public hospitals, Tigray, Ethiopia [22]. However, there is a slight agreement with a report from Tigray region, Ethiopia which was 29.8% [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were poorly adherent to the ART drugs were 2.56 times (AOR = 2.56, 95% CI: 1.97, 3.33) more likely to have viral non suppression as compared with patients with good adherence. Other studies have also reported that poor adherence to treatment is positively associated with virological treatment failure [30, 44, 46]. This is because, as the drug concentration decreases in the blood, HIV RNAs might not be suppressed which in turn leads to increase in viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Some people living with HIV refuse, delay, or interrupt treatment on a variety of bases, and for periods that vary (Persson et al 2016). Others cannot sustain viral suppression even when taking antiretroviral therapies (Kiweewa et al 2019). In the era of treatment as prevention, these groups are being pushed further to the margins of respectability in HIV discourse (Cormier McSwiggin 2017;Lloyd 2018); they should be included in HIV data justice-oriented conversations.…”
Section: Conclusion: Toward Hiv Data Justicementioning
confidence: 99%